Differentiation among the urban poor and their unequal access to basic services : a case study of five katchi abadis in Hyderabad City, Pakistan - Dhanani, Muhammad Rafique; Amin, A.T.M. Nurul; Sheng, Yap Kioe; Weber, Karl E.; Canadian International Development Agency{u2014} Asian Institute of Technology Canadian Universities Consortium / Partnership Project (CIDA/ A IT-CUC/PP) (Bangkok : Asian Institute of Technology, 1989)
The problem of the urban poor in general and environmental condition in the katchi abadis in particular is generally pursued on the implicit assumption that poor constitutes a homogeneous group. This study makes a point of departure from the received theories on the poor by focusing to examine : ( i ) if there exists any meaningful differentiation among the people of k at chi a bad is or not , if there does exist any differentiation then what, are the bases of these differentiation, and ( iii ) if prevailing differentiation leads to any unequal access to the services created for those who live in katchi abadis. To answer these quest ions t, his research has been undertaken in five k at chi a bad is located within Hyderabad city , The sampling method involved a proportionate 20 per cent sample of households in the selected k at chi a bad is. Although the people living in these katchi abadis are poor, the study reveales that considerable differentiation exists among their inhabitants. Differentiation is observed to exist in terms of ethnic composition, occupation, urban experience, education, income as well as affiliation to political parties. It is also found that such differentiation leads to inequality in access to basic services. Locationwise it is found that Mumtaz Colony, located in the planned area of the city has got the highest accessibility to basic services but t, he Frontier Colony, located away from the city centre in an unplanned area, has the least . Ethnicitywise Mohajirs, migrants from India and a communally cohesive and organised group, appears to have better access to these services; whereas Pathans , migrants from N WPP, many of whom are of rural origin, have the least access to the services. Similarly, the formal sector workers compared to their counterparts in the informal sector, appear to have succeeded more in getting the required services . Urban experience also emerges as an important explanation of inequality in access to basic services, i. e. , while the long term residents manage to establish necessary contacts to get, the service connect ions, the recent, rural mi grants appear to fall behind. Household income also emerges as a key factor in explaining the inequality in access to the services . Other notable factor is political affiliation .
A thesis submitted in partial fulfillment of the requirements for the award of the degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1989
Keywords: Urban poor -- Pakistan -- Hyderabad